Urban ethnobotany of Surakarta, Indonesia: a case study of non-edible plants in Gede Hardjonagoro and Kembang Markets - Santhyami, Santhyami; Isnaeni, Fauziah Riska; Agustina, Putri; Agustina, Lina (Ethnobotany Research and Applications, 2024)
Background: Urban ethnobotany studies the interactions of urban societies and the environment, specifically the uses of plants and plant products. The traditional markets in Indonesia are rich sources of data, as is the case in Surakarta, Central Java, which is considered a unique urban society due to the city being the historical capital of the Javanese kingdom of Surakarta Hadiningrat; with significant Chinese, Indian and Arab communities adding to the unique Javanese culture of Surakarta. This study demonstrates the diversity of non-edible plants and their vernacular usage. This study classified non-edible plants into three distinct categories: plants used for traditional ceremonies, decorative plants, and plants utilized for handicrafts. Methods: Data was collected from January to July 2023 collected in two large traditional markets in Surakarta, Gede Hardjonagoro and Kembang through direct observations and interviews and analyzed using an ethnobotanical approach. Results: The results demonstrate 48 species from 29 families of non-edible plants traded in the Gede Hardjonagoro and Kembang markets with a traditional supply chain linking rural hinterlands to urban markets. There is 70.27% similarity of non-edible plants sold in both markets. The similarity stems from the diverse non-edible plants and plant products used as offering in traditional ceremonies. Non-edible plants sold in Gede Hardjonagoro and Kembang Market are sourced from complex supply chains based on traditional supply chains through generations. Conclusion: The various traditional ceremonies and contemporary arts created from the plants showcase Surakarta's vibrant and unique culture. Keywords: Ethnobotany, Non-edible Plants, Surakarta, Urban